The Effect of Wrist Kinesiotaping on Hand Motor Exercise in Fine Motor Skill for Children with Cerebral Palsy - Erna Setiawati (Indonesian Journal of Physical Medicine & Rehabilitation, 2021)
ABSTRACTIntroduction: Kinesiotaping (KT) is one of current method that being used for hands problems in cerebral palsy. The purpose of this study was to evaluate the effect of kinesiotaping at wrist combined with hand motor exercise in fine motor skill for children with cerebral palsy.Methods: The design was simple randomized controlled study pre and post intervention. There were 18 children who divided into kinesiotaping and control group. Subjects in the KT group received hand motor exercise and wrist kinesiotaping. Subjects in control group received only hand motor exercise.Both groups received the exercise for 4 weeks. There were difference in the MACS score which is used to measure fine motor skills in this study. Pre and posttest scores were collected before applying kinesiotaping and after 4 weeks of intervention.Results: Both groups showed an increase in MACS score after 4 weeks intervention. For MACS score, there was statistically significant difference in KT group (p = 0.025), but not statistically significant in control group (p = 0.083).Conclusion: Wrist kinesiotaping can be used for adjunct therapy combined with conventional hand motor exercise for improving manual ability in the hand and fin e motor skill in cerebral palsy.Keywords: Cerebral palsy, fine motor skill, wrist kinesiotaping.